Pemberdayaan Keluarga Family centered Nursing Terhadap Tingkat Kemandirian keluarga Dalam Pencegahan Stunting - Sety Julita (Jurnal Amanah Kesehatan, 2023)
Stunting is a problem of failure to thrive in children under five due to malnutrition, so that the child does not grow like children of his age. Lack of nutrition occurs when the baby is in the mother's womb in the early stages of pregnancy after the baby is born, but the condition of stunting will begin to appear after the baby is born. already 2 years old (Mitra, 2015). The problem of stunting is still found in the Pekan Wonder Community Health Center area, one of the causes of stunting is that families have not been able to carry out care for stunted toddlers independently. This research design uses a quasi experiment with a non-equivalent control group design. A total of 60 respondents were divided into 30 respondents in the intervention group and 30 respondents in the control group. The research sample was a nuclear family with children aged 0-5 years, both father and mother living at home with the toddler. The sampling technique is total sampling, measured using the family independence observation sheet according to Friedman. Data were analyzed using the Wilcoxon sign rank and Mann Whitney tests. The results of this study show that there is a significant difference between the intervention and control groups in the level of family independence after the intervention. The test of different treatment groups using Wilcoxon obtained a p value <0.001 and the test of the difference between treatment and control groups using Mann Whitney obtained a p value <0.001. Discussion: Family empowerment based on family centered nursing can increase family independence in preventing stunting in children under five years.